Children still experience pain during hospital stay: a cross-sectional study from four countries in Europe - V. Vejzovic; J. Bozic; G. Panova; M. Babajic; A-C Bramhagen (BMC, 2020)
Abstract Background Little is known whether children experience pain during hospital stay from the child's own perspective or not. The existing studies tend to be based on a small number of children and therefore have limitations concerning the generalisability of the results. Aim The aim of this study was to describe children's self-reported pain and experience concerning pain management during hospital stay. Methods This study has a quantitative cross-sectional design with descriptive statistics as data analysis. Results A total of 786 questionnaires, Pain in Children in Hospital, were distributed in four countries with the response rate of 75% which was almost equal between countries. Our result showed that 87% (503/579) children at hospital self-reported pain during the past 24 h. Nearly 63% of the children reported a pain score of > 5 the last 24 h. Most of children reported that they had received a question about pain from the hospital staff, and that the staff observed and assessed their pain. Totally 95% reported that they were satisfied with their pain relief during the last 24 h. Conclusion Our study showed that when children were given the possibility to self-report pain, nearly 2/3 expressed that they had experienced pain during hospital stay. However, most of them reported satisfaction with pain management and their pain relief.